STRATEGI KOMUNIKASI ORGANISASI SUKA DUKA KERTA WARGA DALAM MEWUJUDKAN TOLERANSI UMAT HINDU-KRISTEN DI DESA ADAT PILING KECAMATAN PENEBEL KABUPATEN TABANAN - Adnyana, I Made Ananda Kusuma; Sukabawa, I Wayan; Yasa, I Ketut Wardana (Institut Hindu Dharma Denpasar, 2019)
In an effort to maintain harmony between religions, the people of Adat Piling Village have formed an organization called the Joy and Grief Society, whose members consist of Hindus and Christians in the Indigenous Village of Piling.Based on this background there are several issues raised, namely: 1) How do the communication strategies of the Community Grieving Society in realizing the tolerance of Hindus and Christians in the Adat Piling Village Penebel District of Tabanan Regency? in realizing tolerance between Hindus and Christians in Adat Piling Village Penebel District Tabanan Regency? 3) What is the impact of the implementation of the communication strategy of the Grieving Society and Residents towards Hindus and Christians in the Adat Piling Village Penebel District Tabanan Regency.The results of the analysis obtained from this study are: 1) Communication strategies of Organizational Joy and Grief Residents in realizing tolerance between Hindus and Christians in the Indigenous Village of Piling using five types of communication, namely: a) verbal communication, b) non verbal communication, c) interpersonal communication, d) persuasive communication, and e) group communication. 2) The obstacles that exist in the implementation of the communication strategies of the People's Sorrowful Organizations are in the form of physical barriers, differences in mindset, social factors. 3) The impact arising from the implementation of communication strategies of the Community Grieving Society on Hindus and Christians in the Piling Traditional Village includes cognitive impacts, affective impacts, behavioral impacts, and social impacts.